Towards Development a Novel Framework of Web-Based Systems Quality Engineering by the Integration between Information Systems and Software Engineering Theories: Context of Higher Education - Ibrahim Fadhel, Ibrahim Eskandar; Syed Idrus, Syed Zulkarnain; Abdullah, Mohd Syukri Yeoh; Ali Ibrahim, Amani Ali Elmetwaly; Omar, Mazni; Khred, Ahmed (IOP Publishing, 2020)
Nowadays systems failure is the dominant of current research in the fields of information systems and software engineering. The rate of systems fails, and dissatisfying users are high with a lack of appropriate framework that can be used as a success measure in the context. With mix of the results in systems success measure. The organization is in need for a well-defined engineered framework to assist in the success measure of web-based systems. Yemeni south region's universities are facing the problem (dissatisfying users, justifying the cost of implementing systems and measuring its success). This study aims to propose the characteristics of a quality framework suitable for such a purpose and context of developing a novel systems quality framework based on adapting Delone & Maclean 2003, ISO 25010 and Tam to measure the success and quality of these web-based systems. Researchers validated the framework and instrument via 8 academic specialized lecturers in systems and software engineering from (Malaysia, Yemen and India). Researchers then confirmed the translated questionnaire (English to Arabic and back to back translation) with an authorized translation company. Before starting the pilot study, pre-test has been conducted with nine respondents to see if there is any doubts or unclear syntax, everything was OK. Pilot results showed an excellent result.